Sexual health knowledge in female asylum seekers living in New York City: a single-center, cross-sectional study over one year - Andrew R. Milewski; Mary Cox; Samantha Huynh; Gunisha Kaur; Kane O. Pryor; Sheida Tabaie (Inishmore Laser Scientific Publishing Ltd, 2021)
# Background Female asylum seekers remain vulnerable even after resettling in high-income countries. Few studies address sexual health knowledge in this population. This study aims to determine whether female asylum seekers possess less sexual health knowledge than the general female population in New York City (NYC). # Methods A survey evaluating sexual health knowledge was administered to ten female asylum seekers in NYC and to a general population sample of fifty women in NYC. Two-tailed Student's t-tests were employed to evaluate the statistical significance of the differences in knowledge scores between the two groups, and Fisher's exact tests were used to examine associations between categorical variables. # Results On average, female asylum seekers scored 18.8% lower (95% confidence interval, CI=7.3-30.4, *P*=0.002) on sexual and reproductive health questions, 14.0% lower (95% CI=2.8-25.2, *P*=0.016) on contraception questions, 14.3% lower (95% CI=3.5-25.1, *P*=0.011) on questions about sexually transmitted diseases (STDs), and 15.1% lower (95% CI=6.4-23.9, *P*<0.001) overall compared to the control group. Female asylum seekers were, on average, aware of 1.2 fewer (95% CI= 0.1-2.4, *P*=0.040) of the 11 listed contraception methods and of 1.1 fewer (95% CI=0.3-1.8, *P* = 0.006) of the five listed STDs. # Conclusions Female asylum seekers were found to be less knowledgeable about sexual health than a general population of women in NYC. We additionally highlight a feasible strategy for recruiting participants from a population that is traditionally difficult to access.